Práticas de leitura literária nos anos iniciais do Ensino Fundamental: questões sobre a afetividade no processo de leitura - Campos, Josiane Xavier Thelau (2023)
This research aims to analyze the effectiveness of literary reading teaching practices and their contribution to the development of the reader in 4th and 5th grade classes in the public school system of the municipality of Vila Velha, ES, Brazil. It is based on the Wallonian perspective, which advocates for the intertwining of affective and cognitive aspects, considering the child as a whole, as well as on the discussion about the importance of literary reading for the comprehensive development of the child, anchored in the studies of Candido (2011), Geraldi (2017), Colomer (2007), Rouxel (2013), among others. This is a qualitative research conducted in one 4th grade class and one 5th grade class in the municipality of Vila Velha, ES. Data collection involved observing the literary reading activities conducted by the teachers and conducting semi-structured interviews with students and teachers. Through these resources, the aim was to understand the interaction situations and, based on the comments and memories of these subjects about the activities, establish a relationship between the reading experiences in the classroom and the formation of the reader. Four thematic axes were established through content analysis: the itineraries of the teaching practice, the constitution of the reader student, the role of affectivity in the constitution of the reader, and the challenges of teaching practice. Based on these axes, it was possible to identify that the pedagogical decisions made by the teacher in the planning and development of their lessons have a direct impact on how their students engage with literary reading practices, thus contributing to the formation of literary readers in the early years. Furthermore, it was found that interactions are marked by affectivity and, consequently, in the construction of meaning, resulting from the experience of literary reading. However, the continuity of this practice in schools is threatened by the lack of initial and continuous training for teachers, as well as the absence of public policies on literary reading that are not subjugated to market logic, which affects education.